Inuit knowledge and use of wood resources on the west coast of Nunavik, Canada - Steelandt, Stéphanie; Bhiry, Najat; Marguerie, Dominique; Desbiens, Caroline; Napartuk, Minnie; Desrosiers, Pierre (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2013)
Driftwood and shrubs are the primary wood resources available in most areas of coastal Nunavik. Today, they are mainly used as fuel for campfires, but historically they were very important for the ancestors of present-day Inuit. This article documents Inuit traditional knowledge about the origin, availability, gathering, and exploitation of wood resources in this region located in the Low Arctic and the Subarctic. Interviews were conducted with 27 Inuit between 60 and 89 years of age in the villages of Ivujivik, Akulivik, Inukjuak, and Umiujaq on the east coast of Hudson Bay. Our data reveal, among other things, that Inuktitut names for pieces of driftwood were based on shape, aspect, colour, and texture. This traditional knowledge was very accurate and highly diverse in the southern villages because of their significant exposure to driftwood. Wood from shrubs (i.e. willows, birches, and alders) was mainly harvested in the fall and used to make fires, mattresses, sleeping mats (alliat), and other objects. According to the participants, driftwood originates in southern Hudson Bay and James Bay and is washed up on the beaches in late summer and the fall. In the far north of Nunavik, where driftwood is small and slender, Inuit used to collect it during the summer from a boat (umiaq or qajaq). Further south, it was gathered during the winter by dogsled.